1940
DOI: 10.1017/s0022029900017660
|View full text |Cite
|
Sign up to set email alerts
|

258. The Vitamin B1and Riboflavin of Milk

Abstract: With 5 Figures) SYNOPSIS Pait I. The application of Jansen's thiochrome lest to the estimation of vitamin B l m milk. Introduction Experimental The thiochrome test Study of factors influencing the action of takaphosphatase (takadiastase) on milk in the chemical estimation of vitamin Bj Effect of pH. Period of incubation Method of incubation Peptic digestion Tryptic digestion Comparison of the effect of takaphosphatase, pepsm and trypsin preparations on the assay of vitamin B, in milk. The effect of crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1943
1943
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…It is known (Houston, Kon & Thompson, 1940) that in cow's milk vitamin B, occurs in a 'free' form and also bound, much of it phosphorylated. It was of interest to find out the form in which the vitamin was present in sow's colostrum and milk, and for this purpose measurements were made before and after treatment with takaphosphatase.…”
Section: Vitamins Colostrummentioning
confidence: 99%
“…It is known (Houston, Kon & Thompson, 1940) that in cow's milk vitamin B, occurs in a 'free' form and also bound, much of it phosphorylated. It was of interest to find out the form in which the vitamin was present in sow's colostrum and milk, and for this purpose measurements were made before and after treatment with takaphosphatase.…”
Section: Vitamins Colostrummentioning
confidence: 99%
“…The positive correlation between the phosphatase titre and the percentage of the total thiamine present in the free form (Table 4) appears to be general. It was observed by Houston et al (1940) for the milk of cows and goats, and by Braude et al (1947) for sow's milk. Chanda et al (1952) found it to exist in the milk Qf cows treated with thyroxine and thiouracil.…”
Section: I953mentioning
confidence: 84%
“…For estimating chloride the method of Davies (1938) and for phosphatase and the partition of phosphorus the procedures used by were adopted. Total thiamine and the partition of thiamine were determined by a slight modification (Chanda, McNaught & Owen, 1952) of the method described by Houston, Kon & Thompson (1940). The reading for each fraction was made in a Spekker fluorimeter in isobutanol as thiochrome (Jansen, 1936).…”
Section: Methodsmentioning
confidence: 99%
“…Henry, Houston, Kon and Osborne (1939), Houston, Kon and Thompson (1940) arid Henry, Houston, Kon and Thompson (1944) showed that the loss of nutrients in processing was negligible, except of vitamin B, and ascorbic acid. The loss of vitamin R, and ascorbic acid increased on storage.…”
Section: And[ilkmentioning
confidence: 99%